Avoidance learning and classical eyeblink conditioning as model systems to explore a learning diathesis model of PTSD. (May 2019) - Allen, M.T.; Handy, J.D.; Miller, D.P.; Servatius, R.J.
Highlights: Vulnerabilities may determine who does or does not develop PTSD following a trauma. Avoidance is a risk factor for the development of PTSD. Behaviorally inhibited organisms exhibit enhanced avoidance and eyeblink conditioning. Enhanced learning is especially evident in uncertain learning situations. A learning diathesis model of PTSD is supported. Abstract: Experiencing a trauma is necessary, but not sufficient, for the development of post-traumatic stress disorder (PTSD) in that most individuals who experience a trauma do not go on to develop PTSD. This suggests that identifiable vulnerabilities (i.e., diatheses) exist that increase the risk for the development of PTSD. One such factor is the personality temperament of behavioral inhibition (BI). Organisms that exhibit BI were studied in the context of avoidance learning and classical eyeblink conditioning. We present a body of evidence supporting a learning diathesis model in which behaviorally inhibited organisms exhibit enhanced acquisition and resistance to extinction in these tasks. Vulnerable individuals show learning-related enhancements when the learning situation involves some degree of uncertainty. We review the known brain circuitry involved in classical eyeblink conditioning in the context of the learning diathesis model. Finally, the data reviewed here demonstrate the value of studying vulnerability factors in humans and a rodent model using cerebellar-dependent learning tasks for understanding the acquisition and endurance of PTSD symptomatology.